Implementasi Perencanaan (Planning) Program Kerja Laboratorium Keagamaan FITK UIN Raden Fatah Palembang - Leny Marlina; Mursyidah Mursyidah; Nurlela Nurlela; Rusdi Efendi (El-Idare, 2022)
The purpose of this study was to describe the planning (planning) of the work program of the Religious Laboratory of the Faculty of Tarbiyah and Teacher Training at the Raden Fatah State Islamic University (UIN) Palembang. This research is a qualitative research with an intrinsic case study approach. The technique for determining the data source is purposive sampling and snowball sampling. Data collection techniques using observation, interviews, documentation, and triangulation of both data sources and data collection techniques. For data analysis techniques through data condensation, data display, and conclusion drawing/verification. The planning for the work program of the Religious Laboratory has been neatly and systematically arranged, although there are some things that still need further development, especially in the budgeting of several programs. The planning (planning) of work programs so far has been systematic, namely the existence of a common vision between the various elements in the FITK UIN Raden Fatah Palembang environment and the continuity of the program, as well as the synergy of the program with the needs of the community.